Enhancing critical thinking skill by implementing electronic student worksheets based on guided inquiry in natural science subject for elementary school - Setiawan, Mhd Arif; Sriadhi, Sriadhi; Silaban, Saronom (Pascasarjana Universitas Negeri Medan, 2024)
Students’ critical thinking skills currently fall short of the requirements for effective learning in the 21st century, highlighting a need for innovative educational models to help cultivate these skills. This study investigates the enhancement of critical thinking skills among sixth-grade elementary students by using an E-LKPD (electronic student worksheets) grounded in guided inquiry. The study utilized a pretest and posttest non-equivalent control group design, encompassing the full student cohort as the sample. Information regarding students' critical thinking abilities was obtained via a descriptive assessment that satisfied recognized validity and reliability standards. The study results, analyzed with an independent t-test on the N-gain score, show an overall improvement rate of 76.16%, exceeding the 70% threshold for high effectiveness. When analyzed by group, the control group achieved an N-gain of 68.11%, falling in the moderate category, while the experimental group reached an N-gain of 84.21%, showing a huge level of effectiveness. Those results conclude that the guided inquiry-based E-LKPD significantly increased critical thinking skills.